Long-Term Anatomical and Functional Survival of Boston Type 1 Keratoprosthesis in Congenital Aniridia - Dyer, Ariann; De Faria, Alix; Julio, Gemma; Álvarez de Toledo, Juan; Barraquer, Rafael I.; de la Paz, Maria Fideliz (Frontiers in Medicine, 2021)
Purpose: To analyze long-term anatomical survival, functional survival, and complications of Boston Type-1 keratoprosthesis (KPro) in eyes with congenital aniridia associated keratopathy (AAK). Methods: A retrospective review of 12 eyes with congenital aniridia that underwent Boston Type-1 KPro surgery was conducted. Kaplan-Meier analysis was performed. Anatomical and functional success criteria were KPro retention and BCVA ≤ 1.3 LogMAR (≥0.05 decimal) at the end of the follow-up period. Postoperative complications were recorded. Results: Mean preoperative BCVA was 2.1 ± 0.9 (range: 3.8-1) LogMAR, glaucoma was a comorbidity in all cases. Five years after the surgery, the overall retention rate was 10/12 (83.3%) and 50% had functional success. Only 3/12 (25%) of the cases never achieved a BCVA ≤ 1.3 LogMAR. Cumulative probability of anatomical success was 92%, 79%, and 79% after 1, 5 and 10 years, respectively. Cumulative probability of functional success was 57% and 46% at 1 and 5 years, respectively. The mean anatomical and functional survival time was 10 ± 1.3 years (95% IC = 7.5 – 12.3 years) and 3.8 ± 0.9 years (95% IC = 1.8 – 5.8 years), respectively. The most common post-operative complication was retroprosthetic membrane (RPM) formation in 8/16 cases (66%). The mean number of complications per case was 2.4 ±1.8 (0 - 6). Conclusions: Boston Type-1 KPro is a viable option for AAK patients with good anatomical and functional long-term results. Glaucoma is an important preoperative condition that affects functional results. RPM formation seems to have a higher incidence in this condition.